THE NEOTECTONIC STRUCTURE OF INTERMOUNTAIN BASINS OF MOUNTAINOUS ALTAI ACCORDING TO ELECTROMAGNETIC AND GEOLOGICAL DATA - N. N. Nevedrova; A. M. Sanchaa; E. V. Deev; S. M. Babushkin (Геодинамика и тектонофизика, 2015)
The article presents new data on the geoelectrical structure of Chuya, Kuray and Uymon intermountain basins, which are the three largest ones in Mountainous Altai, Russia. Geoelectrical models of the basins were constructed using the data obtained from field studies with application of a complex of electromagnetic methods, including transient electromagnetic, vertical electric soundings and electric tomography. Different amounts of field geoelectric data were collected for each basin. Chuya and Kuray basins are studied better, and their basic geoelectrical models were constructed; however, the structure of their marginal parts is still unclear, and additional measurements are underway there. The structure of Uymon basin has not been properly studied by geophysical methods yet; therefore during 2011–2012 field seasons, it was subject to comprehensive electromagnetic (direct- and alternating-current) surveys carried out with the use of modern equipment sets. Measuring equipment ensured high accuracy and efficiency of field measurements. Software systems for modeling and inversion were applied for quantitative electromagnetic data interpretation based on geological data and parametrical measurements in known profiles. The conclusions are supported by results of joint analysis of the available electromagnetic and geological data and confirmed by multidimensional modeling.